Treatment of aphasia in linguistically diverse populations: current and future directions - Imaezue, Gerald C.; Ajayi, David; Davis, Celine (Frontiers in Psychology, 2025)
Aphasia is a multimodal language disorder that affects individuals across all language cultures, disrupting speaking, listening, reading, writing, and gestural communication. Although aphasia is challenging to manage in monolingual individuals, it becomes even more complex in linguistically diverse populations due to factors such as differences in language-specific features, limited linguistically customizable behavioral therapies and clinicians’ cross-linguistic competence. This critical review examines current and emerging treatment approaches for linguistically diverse populations, highlighting the progression from traditional behavioral interventions to innovative modalities, including state-of-the-art AI-driven and culturally sensitive interventions designed to overcome cultural and linguistic barriers and enhance therapy outcomes. The review emphasizes the growing need for aphasia care specific to linguistically diverse populations, with a focus on personalized treatment strategies and innovations in digital therapeutics that account for cultural and linguistic nuances. Specifically, we advocate for: (1) personalizing restorative aphasia therapies to users’ preferred languages; (2) restorative therapies that leverage universal nonverbal systems and neurobiological modulations as primary treatment modalities; and (3) digital innovations such as multilingual artificial intelligence systems for restorative aphasia therapy, particularly delivered through smartphones. Additionally, ethical considerations—including cultural responsiveness, clinician preparedness, and patient data protection-are discussed to inform future directions in equitable and effective aphasia care. Overall, this study provides insights to guide the development of inclusive and innovative aphasia interventions for linguistically diverse populations.